2004
DOI: 10.2741/1362
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of opioid receptors in the nervous system

Abstract: Three types of opioid receptors exist in the animals, each is encoded by a single gene, i.e., the mu opioid receptor gene, the delta opioid receptor gene, and the kappa opioid receptor gene. However, each opioid receptor gene produces multiple mRNA variants as a result of alternative promoter usages, splicing and/or polyadenylation. As such, a large reservoir of regulatory events has evolved for the control of the production of mRNA variants or differentially modified proteins from each opioid receptor gene. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 135 publications
1
46
0
Order By: Relevance
“…Pharmacological studies have demonstrated the significance of the number (3) of opioid receptors and their subcellular distribution (4)(5)(6)(7) in the manifestation of opioid drugs. Studies of gene regulation have revealed that although transcriptional regulation is critical for cells to express opioid receptor mRNAs (8), these mRNAs are mostly silent and require extensive posttranscriptional regulation for the ultimate production of these proteins (9). Using the opioid receptor (KOR) as a model, we have begun to uncover several posttranscriptional regulatory events important for the expression of KOR protein.…”
mentioning
confidence: 99%
“…Pharmacological studies have demonstrated the significance of the number (3) of opioid receptors and their subcellular distribution (4)(5)(6)(7) in the manifestation of opioid drugs. Studies of gene regulation have revealed that although transcriptional regulation is critical for cells to express opioid receptor mRNAs (8), these mRNAs are mostly silent and require extensive posttranscriptional regulation for the ultimate production of these proteins (9). Using the opioid receptor (KOR) as a model, we have begun to uncover several posttranscriptional regulatory events important for the expression of KOR protein.…”
mentioning
confidence: 99%
“…However, extensive studies of transcriptional regulation of opioid receptor genes (7,8) failed to uncover the mechanisms underlying alteration of receptor number or its protein level in neurons that bear a physiological relevance. Recently, posttranscriptional control for the expression of this gene family has begun to be unraveled, primarily, in studying -opioid receptor (KOR) expression (7,9,10).…”
mentioning
confidence: 99%
“…The complexity of the KOR gene regulatory elements might have contributed to the controversy previously found in the field [i.e., stress-induced KOR mRNA reduction (14) vs. increase (15) in the striatum, no effect (16) vs. increased (15) KOR mRNA in the nucleus accumbens]. To this end, it is important to note that the different isoforms of KOR mRNA exhibit distinct stability, translation efficiency, RNA transport efficiency, and CNS expression patterns (23,37). The current research, demonstrating the effects of stress on KOR epigenetic processes is in line with the indicated ability of external stimuli, including stressors such as forced swim exposure, to affect chromatin remodeling, DNA methylation, and histone modification of stress-associated genes and/or within stress-sensitive brain area (25).…”
Section: Discussionmentioning
confidence: 99%
“…The mouse KOR gene generates three 5′ isoforms, A, B, and C through alternative splicing and promoter use [promoter 1 (Pr1) vs. promoter 2 (Pr2)] (21), and two alternative polyadenylation (PA) sites, PA1 and PA2. By combining 5′ variation and alternative PA use, at least six RNA isoforms can be generated from the KOR gene, each with distinct stability, translation, and transport efficiency, providing a rich reservoir for regulating receptor production and/or distribution (23). The development of neuropathic pain following nerve injury correlates with differential expression of KOR mRNA isoforms (24), and rodent strains with elevated stress susceptibility (1) have differential expression of KOR mRNA isoforms in the cortex, hypothalamus, and locus coeruleus (19,20).…”
mentioning
confidence: 99%